Cost effectiveness of computer tailored and non-tailored smoking cessation letters in general practice: randomised controlled trial. Issue 7299 (9th June 2001) - Lennox, A Scott; Osman, Liesl M; Reiter, Ehud; Robertson, Roma; Friend, James; McCann, Ian; Skatun, Diane; Donnan, Peter T
Abstract: Objectives: To develop and evaluate, in a primary care setting, a computerised system for generating tailored letters about smoking cessation. Design: Randomised controlled trial. Setting: Six general practices in Aberdeen, Scotland. Participants: 2553 smokers aged 17 to 65. Interventions: All participants received a questionnaire asking about their smoking. Participants subsequently received either a computer tailored or a non-tailored, standard letter on smoking cessation, or no letter. Main outcome measures: Prevalence of validated abstinence at six months; change in intention to stop smoking in the next six months. Results: The validated cessation rate at six months was 3.5% (30/857) (95% confidence interval 2.3% to 4.7%) for the tailored letter group, 4.4% (37/846) (3.0% to 5.8%) for the non-tailored letter group, and 2.6% (22/850) (1.5% to 3.7%) for the control (no letter) group. After adjustment for significant covariates, the cessation rate was 66% greater (−4% to 186%; P=0.07) in the non-tailored letter group than that in the no letter group. Among participants who smoked <20 cigarettes per day, the cessation rate in the non-tailored letter group was 87% greater (0% to 246%; P=0.05) than that in the no letter group. Among heavy smokers who did not quit, a 76% higher rate of positive shift in "stage of change" (intention to quit within a particular period of time) was seen compared with those who received no letter (11% to 180%; P=0.02). The increase in cost for each additional quitter in the non-tailored letter group compared with the no letter group was £89. Conclusions: In a large general practice, a brief non-tailored letter effectively increased cessation rates among smokers. A tailored letter was not effective in increasing cessation rates but promoted shift in movement towards cessation ("stage of change") in heavy smokers. As a pragmatic tool to encourage cessation of smoking, a mass mailing of non-tailored letters from general practices is more cost effective than computer tailored letters or no letters.